ANALISIS KANDUNGAN KADAR SERAT DAN KARAKTERISTIK SOSIS TEMPE DENGAN FORTIFIKASI KARAGENAN SERTA PENGGUNAAN TEPUNG TERIGU SEBAGAI BAHAN PENGIKAT - Larasati, Kiki; Patang, Patang; Lahming, Lahming (Jurnal Pendidikan Teknologi Pertanian, 2017)
The objective of the research is to determine the effect of the concentration of the wheat flour as a binder on the characteristics (colour, aroma, taste and texture) and the concentration of carrageenan on the value of nutrients (carbohydrate, protein content and fibber content sausage tempeh) this research employs two steps: the first by treatment with the use of flour 0%, 6%, 8% and 10%, and the best treatment is 10%, and then used in the step II with treatment fortification carrageenan 0%, 2%, 4% and 6%. This research use complete random with three replications. The results showed the concentration of fluorine showed the best result is a concentration of 10%, whereas the concentration of carrageenan sausage the which is 2% on the organoleptic test, test and test fiber carbohydrate protein content test except the treatment on carrageenan without fortification.